Content Management System Development for Medical Web Applications - Adrian, Monterico; Ahmad, Munawar (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
The world of the web and the internet today has become one of the centers for exchanging information between humans, one of which is shown by the development of web applications in the form of content management systems (CMS). By being based on JavaServer Pages (JSP), which has the advantages of being platform-independent, inexpensive and free, and easy to develop, it is possible to become an alternative solution to meet today's general medical needs, namely online and web-based, extensible and customizable. , robust and efficient, secure and authenticated, and easy to develop and maintain. there is a need that turns out to be equally owned and used by only a few medical institutions or there is even a need that is shared by all of them. These needs are developed and used as a standard so that web applications in the medical field are universal and can be used by any medical institution, anywhere, and anywhere. As a result, medical needs that can be implemented into a web application and can be universally applicable.